Prevalence of Caries in Schoolchildren in the Rural Area of a Small Municipality in the South of Minas Gerais, Brazil - Freitas, Érica Michelle Gonçalves de Lima; Maciel, Ivana Maria Esteves; Schiavianato, Larissa Maçais Carvalho; Oliveira, Gleisson Miranda de; Gasque, Kellen Cristina da Silva; Caldeira, Amanda Valentim; Lima, Daniela Coêlho de; Pereira, Alessandro Aparecido (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Introduction: Despite advances in caries treatment, the disease still afflicts populations deprived of access to goods and services. Objective: To determine the prevalence of dental caries as well as the dental treatment needs for children aged five to twelve years old from rural public schools in Alfenas/MG. Material and method: Cross-sectional descriptive observational study, carried out through an epidemiological survey, in which data were collected through clinical examination of 364 children from five rural schools in the city. These tests were performed by a calibrated examiner (intra-observer kappa = 0.93), within the institutions, after signing the Free and Informed Consent Form by the person in charge. The prevalence of caries and the need for dental evaluation were observed, using the DMFT and DMFT-D according to the codes and criteria recommended by the WHO. For data collection and analysis, they were processed in the EPIBUCO program, version 2004. Result: At 5 years of age, there was a prevalence of caries in 70% of the children, dmft of 2.98 and a mean of 2.13 deciduous trees in need of restorative intervention, corresponding to 71.44% of dmft. At 12 years of age, a DMFT of 2.20 and a mean of 0.8 permanent teeth in need of restorative intervention per individual were reported, which represents 36.44% of the index. Conclusion: The results show the high prevalence of caries in children from rural schools, thus showing a worse condition than that observed in the Brazilian population, being also below the O.M.S. goals.